2022
DOI: 10.1002/ppul.26087
|View full text |Cite
|
Sign up to set email alerts
|

Stress and mental health in adolescents and young adults with cystic fibrosis 1 year after the COVID pandemic: Findings from an Italian sample

Abstract: Background: The spread of COVID-19 was associated with increased stress and new mental health concerns for people with cystic fibrosis (pwCF), already at increased risk for depression and anxiety. This study assessed stress and mental health in adolescents and young adults with CF 1 year from when the pandemic began.Methods: Sixty-six pwCF (mean age = 24; range 14-36) completed a new measure of the impact of COVID-19 (COVID-19 Exposure and Family Impact Scale-Adolescence and Young Adult; CEFIS-AYA); the Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Those results differ from that of Graziano et al, where 75% of the study participants manifested symptoms of depression [ 32 ]. In another study by Graziano et al, 45% of CF adolescents and adults scored above the depression cut-off one year after the beginning of the pandemic, which was similar to the results of that population prior to the pandemic [ 25 ]. Although the frequency of depression was higher than in our study, the general tendency was similar—COVID-19 did not influence the occurrence of depression in CF patients.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Those results differ from that of Graziano et al, where 75% of the study participants manifested symptoms of depression [ 32 ]. In another study by Graziano et al, 45% of CF adolescents and adults scored above the depression cut-off one year after the beginning of the pandemic, which was similar to the results of that population prior to the pandemic [ 25 ]. Although the frequency of depression was higher than in our study, the general tendency was similar—COVID-19 did not influence the occurrence of depression in CF patients.…”
Section: Discussionsupporting
confidence: 72%
“…Although the elevated levels of distress were significant, there were no differences in incidences of depression amongst the studied groups [ 24 ]. Similar results were obtained in the study by Graziano et al, where CF patients’ perceived level of stress one year after the onset of the COVID-19 pandemic was rated as moderate; however, their anxiety and depression scores were similar to those before the pandemic [ 25 ]. As CF patients have already dealt with the burden of their disease, the new challenges and threats of the pandemic may have contributed to the deterioration of their mental health.…”
Section: Introductionsupporting
confidence: 86%
“…A longitudinal study in inflammatory bowel diseases patients showed that health-related quality of life was not related to restrictions of the COVID-19 pandemic, but rather to the course of the disease, in relation to its activity phases [28]. Moreover, an Italian study of patients with respiratory chronic disease, showed that after a year from the pandemic beginning, depression and anxiety scores were like rates described for this population before the pandemic [29]. Our results were consistent with these published data.…”
Section: Discussionmentioning
confidence: 90%
“…Nonetheless, at the end of 2020, a prospective Italian study showed that PCD patients suffered from a psychological distress similar to controls; likely because of a low rate of pulmonary exacerbation during follow-up [ 43 ]. In keeping with this, a recent study assessed stress and mental health in adolescents, and young adults with Cystic Fibrosis; the study showed that the depression and anxiety scores were similar before and after the pandemic [ 44 ].…”
Section: Children With Cld and Psychosocial Impact Of Covid-19 Pandemicmentioning
confidence: 99%